ANALISIS KOMPETENSI GURU KIMIA SMA NEGERI KUBU RAYA TERHADAP PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Mirnawati, Nurul Aini; Hairida, Hairida; Masriani, Masriani (Universitas Tanjungpura, 2024)
This study aims to describe the competence of chemistry teachers on the use of Information and Communication Technology in learning at SMA Negeri Kubu Raya. The research method used is a quantitative description. The first step of the research carried out was observation after that data collection was carried out. The data collection technique used here is a questionnaire. The subject of this study was a chemistry teacher at Kubu Raya State High School. There are 22 state schools in Kubu Raya, a sample of 10% is taken, then it is rounded up to 3 schools. The selection of this sample is based on the accreditation of these schools. In this study the questionnaire provided can be used to assess four competencies in chemistry teachers, 1) teacher competence in ICT, 2) teacher pedagogical competence, 3) dedactic competence, and 4) social competence. The results of this study obtained an average number of teachers' competence in ICT by 84%. The second competency, namely the teacher's pedagogical competence, gets an average total score of 80%. For the third competency, namely the teacher's dedactic competence, a total average score of 79%. As well as for social competence the teacher gets a total average score of 80%. From this study, the teacher's understanding of ICT competence has the highest score, which means that the teacher already has the basics of using ICT in learning, while dedactic competence gets the lowest average score.